The Imperial Gridiron : Manhood, Civilization, and Football at the Carlisle Indian Industrial School - Bentley, Matthew, 1984-2018; Bloom, John, 1962- (Book collections on Project MUSE., 2022)
"The Imperial Gridiron examines the competing versions of manhood at the Carlisle Indian Industrial School between 1879 and 1918"--